2014
DOI: 10.5194/se-5-1329-2014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and interaction of driving factors in karst rocky desertification: a case study from Changshun, China

Abstract: Abstract. As the most severe ecological issue in southwest China, karst rocky desertification (KRD) has both threatened and constrained regional sustainable development. Comprehensively understanding the relationship between the evolution of KRD and relevant driving data would provide more information to combat KRD in such complex karst environments. Past studies have been limited in quantifying the relative importance of driving factors influencing fine-scale KRD evolution, and have also lacked insight into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 37 publications
1
56
0
Order By: Relevance
“…Land degradation is a worldwide process that affects all five continents (Masto et al, 2015;Xu and Zhang, 2014;Thomas et al, 2015;Yan and Cai, 2015;Wang et al, 2013;Jafari and Bakhshandehmehr, 2013;Cerdà and Lavee, 1999;Bai et al, 2013). The process of land degradation deprives the quality of natural resources and impairs directly on human society (Izzo et al, 2013) through loss of ecosystem goods and services.…”
Section: Land Degradation In Senegalmentioning
confidence: 99%
“…Land degradation is a worldwide process that affects all five continents (Masto et al, 2015;Xu and Zhang, 2014;Thomas et al, 2015;Yan and Cai, 2015;Wang et al, 2013;Jafari and Bakhshandehmehr, 2013;Cerdà and Lavee, 1999;Bai et al, 2013). The process of land degradation deprives the quality of natural resources and impairs directly on human society (Izzo et al, 2013) through loss of ecosystem goods and services.…”
Section: Land Degradation In Senegalmentioning
confidence: 99%
“…The typical karst areas are characterized by high fragility own to their natural settings and anthropogenic impacts (Xu and Zhang, 2014). This, in turn, has not only damaged eco-environment including soil erosion, lower biodiversity and decreased soil productivity, but also exacerbated the poverty level in the rural areas of the region (Hu et al, 2014;Liu et al, 2005;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The eco-environment of karst mountains is fragile and the land degradation is mainly driven by desertification processes. Generally speaking, lithology and soil type and road influence are identified as the leading factors influencing KRD (Xu and Zhang, 2014;Yang et al, 2013). The succession of KRD has had different impacts on soil fertility indicators ; i.e., the genesis of KRD has been attributed to land mismanagement of local households (Wu et al, 2011) and it has been found that climate change accelerates rocky desertification in the karst areas (Xiong et al, 2009).…”
Section: The Significance Of the Theoretical Model Suggested In This mentioning
confidence: 99%